Identifikasi Air Tanah Dengan Metode Geolistrik Konfigurasi Wenner Di Daerah Perumahan Pesraman Unud Bukit Jimbaran Bali - Ratu, Trivena Sesilia; Wendri, Nyoman; Nurmalasari, Ni Putu Yuni; Putra, I Ketut; Suharta, I Wayan Gede; Baskoro, Winardi Tjahyo (Kappa Journal, 2023)
Identification of groundwater using the geoelectric method in the housing area of the Udayana University boarding house, Bukit Jimbaran, Bali. Data acquisition was carried out using the Wenner configuration to determine the location of the aquifer depth with rock resistivity values. This measurement parameter is the resistivity value of the rock which is then processed using the Res2dinv software for data mapping. After that, aquifer interpretation and geoelectric data interpretation is carried out. The results showed that the aquifer in the residential area of the Bukit Jimbaran Bali Udayana University boarding house is located at a relatively shallow depth of 1.25-12.4 meters below the ground surface. On tracks 1 and 2 have 3 groups of resistivity values. The resistivity value of 2.16–37.5 Ωm with a depth of 1.25-12.4 meters is suspected as a type of tufa lithology. The resistivity value of 72.8–226 Ωm with a depth of 1.25-12.4 meters is suspected to be limestone associated with tuff. The resistivity value of 423–1363 Ωm with a depth of 1.25-12.4 meters is suspected to be limestone.